Hiperglicemia asociada al uso de corticoides en pacientes con COVID-19 - Camacho-Saavedra, Luis Arturo (2023)
Objective: to identify the frequency and magnitude of glucose increase in patients with COVID-19 who received corticoids, Methods: a retrospective study was carried out in adult patients admitted to the COVID-19 hospitalization service of the Hospital EsSalud Virgen de la Puerta, La Libertad, Peru, from April to September 2020. Glucose was identified at baseline and then from the fifth day of corticosteroid exposure. Results: 103 patients were included with a mean age of 62.12 years, 66% male. 49.5% received dexamethasone, 49.5% methylprednisolone and 1% hydrocortisone. Mean glycemia at admission was 109.34 ± 12.89 mg/dl; at day 5 it was 131.61 ±17.66; at day 10 it was 128.10 ± 25.78 mg/dl; at day 20 it was 124.96 ± 27.32 mg/dl; and, at day 30 it was 115.3 ± 29.43 mg/dl. A total of 63.11% of patients presented glycemia higher than 125 mg/dl at day 5 of treatment. Conclusion: glucose levels increased significantly from day 5 to day 20 of corticosteroid treatment in patients hospitalized for COVID-19 and 63% presented glucose levels in the range of diabetes mellitus.